Auditor Tenure and Accounting Conservatism: Testing Moderating Effect of Owner’s Importance - Arabloo, M. D. (Engineering, Technology & Applied Science Research, 2017)
Conservatism is one of the salient features of financial reporting that has attracted more attention in recent years because of financial scandals. Several recent studies have focused specifically on conservatism. This research tries to investigate the effect of auditor tenure and the importance of the client’s accounting conservatism by using panel data model, multivariate regression, and data of 114 companies listed in Tehran Stock Exchange during the years 2011 to 2015. The results showed that there is an inverse relationship between auditor tenure and conservatism of auditees; moreover, the client’s importance has an additive effect on the inverse relationship between auditor tenure and conservatism of client.